A review of 3D printed concrete: Performance requirements, testing measurements and mix design. (1st March 2021) - Hou, Shaodan; Duan, Zhenhua; Xiao, Jianzhuang; Ye, Jun
Highlights: The performance requirements, test methods and mix design of 3DPC are reviewed. The printability and interlayer bond are the keys to study the properties of 3DPC. More accurate test methods and testing standard should be developed. Coarse aggregate and recycled materials need to be considered in the mix design of 3DPC. Abstract: As one of the ways contributing to the progress of the industrialization of the construction industry, 3D printed concrete (3DPC) has attracted more and more attention in recent years. The utilization of 3DPC can accelerate the construction speed, save the labor and raw materials, as well as improve the design freedom of construction without formworks. However, one of the most significant challenges for the application of 3DPC is the printing materials. These is a significant difference in the mixtures and performance between 3DPC and normal concrete. In order to provide an intensive reference for future studies to satisfy the performance requirements of 3DPC structures, this study firstly reviews the performance requirements of 3DPC, including the printability, fresh and hardened mechanical properties, and durability. Based on this, the specialized test methods for 3DPC are reviewed for the effective quality evaluation of 3DPC. The last part presents a review of mix design from the point of view of different materials and mix design approaches. The results show that 3DPC needs to meet the printability that it has higher requirements for rheology, hydration, and green strength than normal concrete. The interlayer bond is the key to study the anisotropic strength and durability degradation. More accurate test methods and testing standards should be developed. Besides, coarse aggregates and recycled materials need to be considered in the mix design of 3DPC.